Alte und neue Formen im Flurbild des Endmoränenbereiches südlich von München - Borcherdt, Christoph (ERDKUNDE, 1953)
The paper deals with some peculiar examples of „Gewannfluren (open fields) in the area south of Munich which owe their distinctiveness to historical reasons; it also raises the question of hedgerows and fences. These arose in response to the technical requirements of the agricultural system, and as late as the early 19th century made a decisive imprint on the rural scene. In this respect there appear to be marked contrasts between the conditions found in South Bavaria and those in South Württemberg. Finally the author discusses the extent of „Egartenwirtschaft or „Wechselwirtschaft (a ley farming with long leys) both as it existed at the beginning of the 19th century and as it does at the present day. These phenomena suggest an approach to a future classification within the broad framework of systematic agricultural geography.